Amir Nasrullo Bukhara Amirligi Rule of Period (Zien Journal of Social Sciences and Humanities, 2022)
Nasrullah (Nasrullah, Nasrullah, Amir Nasrullah, Amir Sayyid Nasrullah, Amir Sayyid Nasrullah Bahodirkhan) (June 1, 1806, Bukhara, Bukhara Emirate - September 21, 1860, Bukhara, Bukhara Emirate) [1] - Ruler of the Bukhara Emirate (1827-1860). A statesman and a commander. [2] The Mangits are the 7th ruler of the Uzbek dynasty and the 5th emir of this dynasty. This article covers the reign of Amir Nasrullo Bukhara.